2012
DOI: 10.1016/j.neurobiolaging.2010.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of differential lymphocyte cell cycle activity in Alzheimer's disease

Abstract: Mounting evidence suggests cell cycle dysregulation is involved in the pathogenesis of Alzheimer's disease (AD) and that this failure is systemic, affecting not only neurons but also peripheral blood lymphocytes (PBLs). This study analyzed if differences in PBL proliferation activity could be used as a diagnostic biomarker for AD. CD69 and CD28 expressions on PBL T, B, and monocyte cells were measured by flow cytometry with and without mitogenic stimulation in healthy controls (HC), probable AD, and Parkinson'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Using univariate models in AD subjects eleven CD expression markers were found to be significantly changed compared with a mixed pool of HC and PD subjects [59]. The results suggest future science group www.futuremedicine.com…”
Section: Dysregulated Cell Cycle In Lymphocytesmentioning
confidence: 82%
See 1 more Smart Citation
“…Using univariate models in AD subjects eleven CD expression markers were found to be significantly changed compared with a mixed pool of HC and PD subjects [59]. The results suggest future science group www.futuremedicine.com…”
Section: Dysregulated Cell Cycle In Lymphocytesmentioning
confidence: 82%
“…Using univariate models in AD subjects eleven CD expression markers were found to be significantly changed compared with a mixed pool of HC and PD subjects [59]. The results suggest future science group www.futuremedicine.com that both for the pathomechanism of AD and the development of AD diagnostic markers, a systemic failure of cellular proliferation control is critically important.…”
Section: Dysregulated Cell Cycle In Lymphocytesmentioning
confidence: 88%
“…46,[52][53][54] For this reason, peripheral cells, such as fibroblasts or blood lymphocytes, have been used extensively in the search for useful biomarkers that may correlate with expression and/or progression of disease. [55][56][57][58] In this regard, it has been shown that peripheral cells from patients with neurodegenerative disorders display cell cycle disturbances, 45,[59][60][61][62] reflecting the unscheduled cell cycle re-entry of postmitotic neurons and leading to apoptotic cell death. [63][64][65] The present work was undertaken to elucidate possible mechanisms involved in the PGRN deficiencyinduced WNT5A expression and signalling in PGRNdeficient lymphoblasts from patients with FTLD-TDP that were considered responsible for the increased activation of the CDK6/pRb-mediated cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Sultana et al, 2011; Stieler et al, 2012), we did not distinguish among subclasses. However, we argue our data are not the product of any small subclass of leukocytes because the vast majority of cells were immunopositive (Fig.…”
Section: Discussionmentioning
confidence: 61%